2012
DOI: 10.1038/srep00496
|View full text |Cite
|
Sign up to set email alerts
|

T1R3: A human calcium taste receptor

Abstract: Many animals can detect the taste of calcium but it is unclear how or whether humans have this ability. We show here that calcium activates hTAS1R3-transfected HEK293 cells and that this response is attenuated by lactisole, an inhibitor of hT1R3. Moreover, trained volunteers report that lactisole reduces the calcium intensity of calcium lactate. Thus, humans can detect calcium by taste, T1R3 is a receptor responsible for this, and lactisole can reduce the taste perception of calcium by acting on T1R3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 28 publications
1
52
0
1
Order By: Relevance
“…A Ca 2ϩ -binding pocket was proposed to be present in the ligand-binding site of the GABA B receptor (55). Many animals and humans can detect the taste of calcium via a calcium taste receptor that is modulated by an allosteric mechanism (69).…”
Section: Discussionmentioning
confidence: 99%
“…A Ca 2ϩ -binding pocket was proposed to be present in the ligand-binding site of the GABA B receptor (55). Many animals and humans can detect the taste of calcium via a calcium taste receptor that is modulated by an allosteric mechanism (69).…”
Section: Discussionmentioning
confidence: 99%
“…242 ). Curiously, Ca 2+ appetite in mice 243 and humans 244 is associated with taste receptor type 1 member 3 (T1R3), which underlies sweet and umami tastes, rather than with CaSR. It remains unclear whether Ca 2+ produces a consciously perceived taste that drives appetite.…”
Section: Figurementioning
confidence: 99%
“…It has been suggested that the T1R3 homodimer is not functional; this notion is based on observations obtained in HEK cells expressing T1R3. 6,7) Nonetheless, a recent study by Tordoff et al 24) demonstrates that T1R3 alone expressed ectopically in HEK cells is indeed functional. We have also shown that T1R3 alone expressed in HEK cells functions as a signaling receptor.…”
Section: Sweet Taste Receptor Functions As the Glucose-sensing Receptmentioning
confidence: 99%